Enhancing HAR Novelty Detection with Activity Confusion Analysis and Clustering - Sousa, Thaís B. de M. B. de; Cruz, Lívia A.; Souza, Criston P. de; Magalhães, Regis P.; Macêdo, José A. F. de (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2025)
The field of medicine and healthcare, especially Human Activity Recognition (HAR), has been experiencing the benefits of technology for tracking people’s habits. In this context, novelty detection aims to detect if an activity performed by a subject hasn’t been seen before, in the past training data. However, the novelty may not be properly recognized if there is a similar action in the train set. Thus, this work proposes an analysis of activity pairs to determine which pairs are most confused when using three traditional models for novelty detection: Local Outlier Factor, One-class SVM, and Isolation Forest. After that, we employ agglomerative clustering to gather similar activities, and the clustered activities are used as input to a leave-one-activity-out novelty detection approach. We conclude that the Isolation Forest model achieves the best results in the activity pairs analysis, yielding an F1 score of 88.4%. Finally, the leave-one-activity-out methodology is evaluated with a sliding window technique, and the F1 score on the Local Outlier Factor model increases from 66.3% (without grouping similar activities) to 74.6% (grouping similar activities).